2011
DOI: 10.1007/s00442-011-2122-x
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure during egg laying is equal for early and late breeding free-living female great tits

Abstract: In many bird populations, variation in the timing of reproduction exists but it is not obvious how this variation is maintained as timing has substantial fitness consequences. Daily energy expenditure (DEE) during the egg laying period increases with decreasing temperatures and thus perhaps only females that can produce eggs at low energetic cost will lay early in the season, at low temperatures. We tested whether late laying females have a higher daily energy expenditure during egg laying than early laying fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Ambient temperature influences daily energy expenditure during egg laying directly and indirectly by affecting thermoregulatory costs and foraging behaviour (Stevenson and Bryant 2000, te Marvelde et al 2012). Low temperature was repeatedly shown to correlate with smaller clutch sizes and/or smaller eggs in various wild bird species (Christians 2002), including the great tit (Nager and van Noordwijk 1992, Nager and Zandt 1994, Lessells et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature influences daily energy expenditure during egg laying directly and indirectly by affecting thermoregulatory costs and foraging behaviour (Stevenson and Bryant 2000, te Marvelde et al 2012). Low temperature was repeatedly shown to correlate with smaller clutch sizes and/or smaller eggs in various wild bird species (Christians 2002), including the great tit (Nager and van Noordwijk 1992, Nager and Zandt 1994, Lessells et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Monaghan, Nager & Houston (1998) have shown that female lesser black‐backed gulls ( Larus fuscus ) that had experimentally increased costs during egg laying (by producing more eggs) had reduced offspring rearing capacity in the nestling stage. For 27 of the 28 females of which we measured DEE during chick feeding, we also measured DEE during egg laying (te Marvelde et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Timing of breeding might be constrained by high energetic demands for egg laying (te Marvelde, Webber, Meijer, & Visser, ; Monaghan & Nager, ) as resources are scarce and temperatures low early in the season. Daily energy expenditure did not differ between wild early and late breeding females during egg laying (te Marvelde et al, ), and females selected for early breeding may thus have a lower BMR, that is leaving more energy to produce eggs. As BMR is heritable in birds (Nilsson, Åkesson, & Nilsson, ; Tieleman et al, ), it could potentially respond to selection on timing of breeding if these traits are genetically correlated.…”
Section: Introductionmentioning
confidence: 99%